Isolation and characterization of Anoxygenic phototrophs from shrimp ponds in Thailand - Ramirez, Xelimar; Luamanu, Imeleta; Michael Ceballos, Ruben; Padilla Crespo, Elizabeth (Access microbiology, 2020)
Anoxygenic phototrophic purple bacteria are ubiquitous in aquatic and terrestrial environments and demonstrate broad phenotypic diversity. Purple bacteriaderive energy from light under anaerobic conditions via anoxygenic photosynthesis, a process in which water is not the electron donor. It has been suggested that these bacteria are useful for a variety of applications, including: wastewater treatment; heavy metal remediation; nitrogen fixation; and, control of CH4 emissions. In this study, the goal was to isolate and characterize PNSB from shrimp ponds in Thailand. Surface water and sediment were collected. Enrichment cultures were prepared using Pfenning’s mineral media. As indicated by development of reddish color and turbidity, anoxygenic phototrophic growth was observed within two days of incubation. Cultures in liquid media and on solid plates exhibited a deep red or purple color ten weeks post-inoculation. Under light microscopy, enrichments consist of communities dominated by thin, elongated gram-negative cells with granules of elemental sulfur, which are characteristic of purple bacteria. Molecular methods confirm the presence of pufLM, a genetic biomarker for purple bacteria (e.g., Thiohalocapsa marina, Allochromatium vinosum, Roseovarius tolerans). Initial sequencing of key genes (i.e., pufLM) indicate that these environmental samples contain novel isolates or “geographic variants” that have not been previously described. We have developed a few pure cultures of multiple species from these environmental samples. Since shrimp farming is a key industry in southern Thailand, the characterization of the microbial communities in these ecosystems, including anoxygenic phototrophs, will provide insights into how to maintain water quality in these food production systems.